Adrenergic stimulation amplifies the difference in beat-to-beat variability between the scar border zone and remote region. (19th May 2022) - Vermoortele, D; Amoni, M; Ingelaere, S; Holemans, P; Menten, R; Willems, R; Sipido, KR; Claus, P
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): KU Leuven BOF-C1 "Blood pressure induced premature ventricular beats as triggers for ventricular arrhythmia in ischemic cardiomyopathy" Background: Myocardial infarction (MI) results in a dense scar region surrounded by a heterogeneous region of fibrosis and remodeled myocytes called the border zone (BZ). Beta-adrenergic stimulation results in increased beat-to-beat variability of repolarization (BVR) which could increase spatial heterogeneity and arrhythmia vulnerability. Objective: To examine the effect of adrenergic stimulation on the beat-to-beat variability in the BZ, compared to the remote region, using novel methodology for determining spatially dense activation-repolarization intervals. Methods: Anterior-septal myocardial infarction (MI) was induced in 10 domestic pigs by 120-minute occlusion of the left anterior descending artery followed by reperfusion. Electro-anatomical mapping was performed after one month. The BZ was defined using contact mapping as the region with bipolar voltage between 0.5 and1.5mV. A non-contact recording of a 64-electrode array was translated to 2048 non-contact electrograms distributed over the LV (EnSite PrecisionTM, St. Jude/Abbott Medical). Electrophysiological recordings were made during baseline and during an isoproterenol (ISO) infusion (incremental doses of 0.01µg/kg until 0.04µg/kg). In each of the 2048 points non-contact electrograms over 25 consecutive beats were processed to determine the BVR using a custom-made algorithm, validated against monophasic action potential recordings. Results: During baseline conditions the maximal BVR was increased in the BZ compared to the remote region (BZ: 3.28±0.90 ms vs remote: 2.61±0.67 ms, P=0.002). During ISO infusion the maximal BVR was also increased in the BZ (BZ: 3.55±0.74 ms vs remote: 2.21±0.60 ms, P<0.001). During baseline the BZ exhibited a larger spatial variance of BVR than the remote region (BZ: 0.20±0.11 ms2 vs remote: 0.087±0.055 ms2, P=0.002). During ISO infusion the spatial variance of BVR was larger in the BZ (BZ: 0.23±0.12 ms2 vs remote: 0.083±0.056 ms2, P=0.001). The maximal BVR was not significantly different during baseline and ISO in the BZ, nor the remote region (P>0.05). However, the difference of the maximal BVR between BZ and remote regions was significantly increased during ISO (baseline: 0.67±0.48 ms vs ISO: 1.34±0.49ms, P=0.001). Conclusion: The MI BZ showed increased temporal heterogeneity in repolarization that could serve as functional substrate for re-entry. Adrenergic stimulation amplified this vulnerability by increasing the difference in maximal BVR between BZ and remote regions.